Issues and challenges in instrument adaptations: Bias and equivalence - Awang Hashim, Rosna (Universiti Utara Malaysia, 1999)
For most of the twentieth century, interest in translating/adapting tests with a second language and cultural group has been prevalent among educational and psychological researchers. The globalization of economy, tourism, migration streams,and related political changes have witnessed the steady increase of publications that concern cross-cultural differences and comparisons (see van de Vijver & Leung, 1997;van de Vijver & Tanzer, 1997). However, this healthy development is not without methodological inadequacies. Despite significant advances in the methodologies that are used to adapt instruments, there remain a number of difficult and challenging issues in this area, which might invalidate generalization of research findings.This paper will examine issues and challenges in instrument adaptations with emphasis on the issues of construct bias and equivalence. Specific reference to the International Test Commission (ITC) test adaptations guidelines (Hambleton, 1999) will be highlighted.Remedies to these problems will be discussed to enhance validity of adapted instruments.